School Transfer to Support Reintegration of Juveniles Involved in Inappropriate Photo-Sharing - Situmeang, Ampuan; Hutauruk, Rufinus Hotmaulana; Alhakim, Abdurrakhman; Febriyani, Emiliya (Kosmik Hukum, 2025)
One the negative usages of digital technology is the sharing of inappropriate photo to someone online. However, as social media users are often the target of doxing, young persons who commit this offense can also be considered victims, leaving them vulnerable to bullying, especially in their own environment, such as school. Using normative legal research method and statutory approach, this research analyzes the potentials of school transfer as a post-criminal proceedings method for juveniles who commit sexual offense in the form of inappropriate photo-sharing, to first get them to an environment safe enough for them to be educated on their mistakes in another school, which is important for their growth. This study identifies normative gaps within the Juvenile Justice, Pornography, and Education Laws that hinder the reintegration of juveniles involved in online sexual offenses, proposing school transfer as a mitigative strategy against bullying and harassment. It emphasizes the need for further research to address implementation challenges, underscoring the importance of a holistic restorative justice approach.